Development of Electronic Module (E-Module) Based on Case Method in Science Subjects at Junior High School - Hendrawensi; Hidayati, Abna; Yeni, Fetri; Zurwina (Jurnal Penelitian Pendidikan IPA, 2024)
This study was conducted with the objective of creating an electronic module (E-Module) using the case method for the Science subject, specifically focusing on the topic of Force and Motion. The E-Module is structured in alignment with an independent curriculum, aiming to enhance students’ academic achievements. The research methodology employed in this study is Research and Development (R&D), following the Analysis-Design-Development-Implementation-Evaluation (ADDIE) model. Expert evaluations of the content of the electronic module (E-Module) based on the case method reveal that the module falls within the "Highly Valid" category, with an average score of 92.14%. Assessments by media experts on the electronic module (E-Module) using the case method also classify it as "Highly Valid," with an average score of 92.14%. Similarly, language experts’ evaluations, categorizing it as "Highly Valid," yield an average score of 90.90. These findings indicate that each aspect of the electronic module (E-Module) is deemed valid and meets the criteria for high validity. Consequently, it can be inferred that the electronic module (E-Module) based on the case method is well-suited for use as a teaching tool incience instruction for seventh-grade junior high school students.